Analysis of Students’ Misconceptions on Acid-Base Topic Using the Two-Tier Diagnostic Test - Fika Rakhmalinda; Risna Arifiani; Woro Puspawati; Aprianta Magdalena Simamora (Scientia Publica Media, 2024)
This case study aims to explore the misconceptions surrounding acid-base concepts. It utilizes a qualitative descriptive research design to examine students’ comprehension of the acid-base concept. The sample includes 231 students from grades XI and XII in the science stream who have studied acid-base, selected randomly from SMAN 54 Jakarta and SMAN 14 Bekasi schools. The methodology involves the use of a two-tier diagnostic test tool, interviews, and reflective journals. The research tool consists of a two-tier diagnostic test with 10 hierarchical questions - multiple-choice at the first level and reasons for the first-level answers at the second level, totaling 20 questions adapted from a previous study (Ibrahim, 2016) to ensure validity and reliability. The diagnostic test tool was administered to students through Google Forms. The study findings from 231 participants showed that 44% of students grasped the acid-base concept, 19% had a partial understanding, 17% held misconceptions, 20% did not understand, and 19% did not provide a response. The research results were corroborated by interviews and reflective journals with students who took part in the two-tier diagnostic test. The identification of misconceptions in acid-base material highlights the necessity to enhance teaching approaches, stressing the significance of teachers recognizing the individual learning styles of their students.